Novel multiplex PCR assay for identification and subtyping of enteroinvasiveEscherichia coliand differentiation fromShigellabased on target genes selected by comparative genomics. Issue 9 (September 2018) - Dhakal, Rajat; Wang, Qinning; Lan, Ruiting; Howard, Peter; Sintchenko, Vitali
Abstract : Purpose. : Both Shigella and enteroinvasive Escherichia coli (EIEC) can cause enterocolitis, but they have a distinct epidemiology and public health relevance. Current culture‐independent testing (CIT) methods to identify Shigella in faecal samples rely on the ipaH gene as the target, which is also found in EIEC genomes. The aim of this study was to design an assay that can identify EIEC in cultures from CIT ipaH ‐positive samples. Methodology. : Shigella and EIEC genomes were screened to find unique regions present in EIEC genomes using a comparative genomics approach and differentiating genetic loci that are suitable PCR targets were identified. The primers for these loci were designed and tested in 6501 and 104 genomes of Shigella and EIEC, respectively. Results. : An assay with two sets of multiplex PCR reactions that differentiates Shigella and EIEC based on the presence/absence of at least two out of six loci was developed and evaluated. The majority of Shigella genomes lacked all six loci, while at least two loci were present in most EIEC genomes. This assay successfully differentiated clinical EIEC from Shigella with a limit of detection of 10 5 cells ml −1 . The sensitivity and specificity were over 95 and 99%, respectively. The assay can further subtype EIEC genomes into their genetic lineages. Conclusion. : This new highly specific assay can assist in the identification of EIEC in ipaH PCR‐positive samples and augment the public health laboratory surveillance of EIEC and shigellosis.